2021
DOI: 10.3390/ijerph181910015
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Status and Training Load in Women Soccer Players

Abstract: This study aimed to analyze the variations of fitness status, as well as test the relationships between accumulated training load and fitness changes in women soccer players. This study followed an observational analytic cohort design. Observations were conducted over 23 consecutive weeks (from the preseason to the midseason). Twenty-two women soccer players from the same first Portuguese league team (22.7 ± 5.21 years old) took part in the study. The fitness assessment included anthropometry, hip adductor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…Suporting our results, recent studies demonstrated that sprint performance gradually improved over the course of the season in elite youth soccer players [4,55]. On the contrary, previous studies found that sprint performance (10 m, 30 m) did not change significantly during a season in elite female soccer players, which is not compatible with the results of our study [53,56]. Furthermore, multiple linear regression analysis revealed that maturity had no significant effect on the change in velocity performance during the season in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Suporting our results, recent studies demonstrated that sprint performance gradually improved over the course of the season in elite youth soccer players [4,55]. On the contrary, previous studies found that sprint performance (10 m, 30 m) did not change significantly during a season in elite female soccer players, which is not compatible with the results of our study [53,56]. Furthermore, multiple linear regression analysis revealed that maturity had no significant effect on the change in velocity performance during the season in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Analyzing the probability of associations between accumulated training load and changes in sprint performance helps determine whether training load is a determinant of these changes or if there are other factors that coaches should be aware of [53]. Having good physical capacity during the season also increases tolerance to training load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COD ability has shown to discriminate between levels of performance (Kutlu et al, 2017;Kaplan et al, 2009) with males compared to females showing faster performances (Mujika et al, 2009). More so, COD ability has shown to predict high intensity accelerations and decelerations on a match (Gonçalves et al, 2021). It is therefore not surprising that COD ability is habitually targeted by practitioners as a physical capacity to enhance through specific training methods (De Keijzer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From those km, high-intensity running (18-25 km/h) demands can vary between 718 [4] and 3000 m [5]. These range values are dependent from competitive level, playing position, age-group or event moment of the season and physical fitness [6,7].…”
Section: Introductionmentioning
confidence: 99%